Back Cover: Assessment of DNA Binding to Human Rad51 Protein by using Quartz Crystal Microbalance and Atomic Force Microscopy: Effects of ADP and BRC4‐28 Peptide Inhibitor (ChemPhysChem 17/2014). Issue 17 (1st December 2014) - Esnault, Charles; Renodon‐Cornière, Axelle; Takahashi, Masayuki; Casse, Nathalie; Delorme, Nicolas; Louarn, Guy; Fleury, Fabrice; Pilard, Jean‐François; Chénais, Benoît
<x xml:space="preserve">Abstract</x> The modification of gold surfaces by the reduction of aryldiazonium salts, and the subsequent immobilization of single‐stranded DNA are described by J.‐F. Pilard, B, Chénais, et al. on p. 3753. The interaction of HsRad51 protein with DNA was then studied using quartz crystal microbalance (QCM) and atomic force microscopy (AFM).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>